Tecnologia de aplicação: uma análise sobre a eletrostática - Halberstadt, Tailine (2023)
Agriculture has demanded the development of technologies to improve processes in search of greater quality and profitability of agricultural crops, better performance in the field, being economically viable and safe, in this sense electrostatic spraying has enabled greater efficiency in phytosanitary applications. The objective of this work was to present a systematic review on the subject, which is still not very widespread, as well as a analysis with case studies carried out with the TSBJet® electrostatic spraying technology in the central region of Rio Grande do Sul. The technology was installed in boom sprayers, isolating one side of the boom, so that the conventional application was maintained, in order to better assess the reality of the application in the comparison between both. For this purpose, hydrosensitive papers (Syngenta®) were distributed in the soil, lower, middle and upper stratum of the plant, subsequently read and interpreted by the DropScope® equipment. The results showed that the technology improved the coverage of drops in the three strata of the plant, which demystifies the phenomenon called “antenna effect” in which drops with an electrostatic charge remain only in the upper stratum. In addition, it enables drift reduction, greater environmental safety and better performance of agricultural pesticides used especially in plant protection, findings that corroborate the theoretical framework presented.